2012
DOI: 10.1242/dev.081471
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale mechanisms of cell migration during development: theory and experiment

Abstract: models, cell movement is encouraged by cell-cell contact, which may be manifested as nudging from behind (Davis and Trinkaus, 1981) or the detachment of cells at the front of a migratory cell sheet (Carmona-Fontaine et al., 2008) to create space. These cell behaviors alone may not produce directional movement of a multicellular stream, but when local inhibitory signals restrict cell movements the result can be long-distance directed cell movement.By contrast, other models suggest that cells respond to chemotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(223 citation statements)
references
References 41 publications
7
215
0
1
Order By: Relevance
“…Recent studies have found that co-attraction between cells may play a role in collective migration [26,27]. This is also consistent with the framework of flocking models [9,10].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recent studies have found that co-attraction between cells may play a role in collective migration [26,27]. This is also consistent with the framework of flocking models [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…In loosely associated stream-like migration cell protrusions transmit biochemical signals. For neural crest cells, whose migration shares many characteristics with metastatic cancer cells, such interactions provide directional guidance that leads to coordinated migration even in the absence of external chemoattractant [6,[25][26][27]. When two cells touch a chemical exchange occurs and in response to this signalling, the protrusions at the site of contact collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The migration of cells on or through extracellular matrix (ECM) as well as cell-mediated remodeling of ECM underlie many biological processes including development [1], growth and remodeling [2], fibrotic pathologies [3], and wound healing [4] and are also important components of many tissue engineering applications [5,6]. In addition to chemical means such as the synthesis, modification, and degradation of the matrix, cells remodel (i.e., reorganize existing material) ECM using mechanical (or traction) forces.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in silico modeling has proposed that a balance of coattraction and CIL is important for the directional migration of NCCs (Woods et al, 2014). Other modeling suggests that NCCs may have two general roles: leader cells located toward the front of the migratory stream and follower cells trailing behind the leaders (McLennan et al, 2012). Based on this computational model, leader cells would respond more to long-range signals within the microenvironment, while follower cells would respond to short-range signals coming from NCCs ahead of them (McLennan et al, 2012).…”
Section: Migratory Mechanisms and Communicationmentioning
confidence: 99%